Ruthenium-catalyzed deaminative hydrogenation of amino nitriles: direct access to 1,2-amino alcohols - Calleja Ramos, Pilar; Hashmi, A. Stephen K. (Chemistry - a European journal, 2019)
A new approach for the efficient and highly selective synthesis of 1,2-amino alcohols by direct reductive hydrolysis of N-formyl-protected α-amino nitriles is reported. The commercially available RuHCl(CO)(PPh3)3 complex was found to be a suitable catalyst for this operationally simple protocol, in which no stoichiometric amounts of undesired metal waste are generated. The deaminative hydrogenation is performed at 55 bar of H2, using a 6:1 mixture of 1,4-dioxane/water as solvent. In addition, hydroxymethyl alcohols were prepared from cyanoketones under very similar conditions.